Foot Length as a Proxy Indicator for Detection of Birth Weight in Newborns: An Observational Cross-sectional Study - Daasara Gururaju; Manjunathswamy Rangappa; Bheemaraya Shivasharana (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Birth weight is an important parameter to assess the overall wellbeing of newborn. In developing countries like India, where large number of home deliveries occurs measuring birth weight is difficult. Studies have reported a positive correlation between birth weight and foot length. Hence, foot length may be considered as an alternative in place of birth weight, the former being an easy and cheap parameter to assess. Aim: To assess the correlation between foot length and birth weight in newborns, delivered or referred within 24 hours of birth. Materials and Methods: This observational cross-sectional study was conducted in Neonatal Intensive Care Unit (NICU) at Shimoga Institute of Medical Sciences, Karnataka, India, (tertiary care hospital), from February 2021 to October 2021. A total of 902 newborns were included in the study. Foot length was measured with transparent ruler scale with 0.1 cm precision, and birth weight was recorded using digital weighing scale with 10 grams precision. The correlation coefficient was calculated between foot length and birth weight. Results: Out of 902 newborns, 495 (54.87%) were males. The mean birth weight was 2.57±0.56 kg. The mean foot lengths were 7.27±0.58 cm in <2.5 kg category, 7.3±0.47 cm in 2.5-3.5 kg category, and 7.82±0.48 cm in >3.5 kg category. The correlation coefficient between foot length and birth weight in <2.5 kg, 2.5- 3.5 kg and >3.5 kg group were 0.96, 0.93 and 0.78, respectively. Conclusion: Foot length can be used as a proxy measure to detect low birth weight in newborns in resource-limited settings where weighing is not possible.